(untitled) (Research, Society and Development, 2021)
Protected areas are essential for the maintenance of biodiversity. In Brazil, national parks encompass one of the most important portions of this area (26.864.003,74ha) that needs to be adequately managed to achieve conservation. Aiming to understand how the ichthyofauna data is included in management plans of Brazilian National Parks, we review 55 Brazilian national parks management plans to compare how data of freshwater fish fauna are included in these documents. The data evaluated from management plans were Hydrography, ichthyofauna list, participation of professionals trained in rapid ecological assessment and species richness, endangered and invasive species. This information was used to categorize the management plans through two sets of assessing: quality of rapid ecological assessment and coverage of species diversity. The categorization results were assumed as an indicator of the potential for biodiversity conservation of the management plans. We compare obtained results between biomes. We were able to understand that many of the Brazilian National Parks do not have management plans, and among the plans that are prepared, the lack of essential information compromises their potential for the conservation of biodiversity. We highlight the need to improve management plans for the Caatinga parks and expand the analysis of invasive species for all biomes.